Modification of DS-01 Drilling Fluid to Reduce Formation Damage - Winarto S.; Sugiatmo Kasmungin (Journal of Earth Energy Science, Engineering, and Technology, 2019)
In the process of drilling for oil and gas wells the use of appropriate drilling mud can reduce the negative impacts during ongoing drilling and post-drilling operations (production). In general, one of the drilling muds that are often used is conventional mud type with weighting agent barite, but the use of this type of mud often results in skin that is difficult to clean. Therefore in this laboratory research an experiment was carried out using a CaCO3 weigting agent called Mud DS-01. CaCO3 is widely used as a material for Lost Circulation Material so that it is expected that using CaCO3 mud will have little effect on formation damage or at least easily cleaned by acidizing. The aim of this research is to obtain a formula of mud with CaCO3 which at least gives formation damage. Laboratory experiments on this drilling mud using several mud samples adjusted to the property specifications of the mud program. Mud sample consists of 4, namely using super fine, fine, medium, and conventional CaCO3. First measuring mud properties in each sample then testing the filter cake breaker, testing the initial flow rate using 200 ml of distilled water and a 20 micron filter disk inserted in a 500 ml HPHT cell then assembled in a PPA jacket and injecting a pressure of 100 psi. The acidification test was then performed using 15% HCL and then pressured 100 psi for 3 hours to let the acid work to remove the cake attached to the filter disk (acidizing). Laboratory studies are expected which of these samples will minimize the formation damage caused by drilling fluids.